Need for Sensitization on Serious Threats of Second-Hand Smoke: Findings from a National Study in Mauritius, a Small Island Developing State in the Indian Ocean - Chan Sun, Marie; Beeharry Panray, Urmila Devi; Cheeneebash, Jayrani; Gunesh, Raj (Elsevier, 2022)
This study had the following objectives: To assess the level of knowledge of Mauritians aged ≥ 20 years on the health effects of Second Hand Smoke (SHS), to investigate their behaviour when exposed to SHS and to look for any association between SHS-related knowledge and behaviour towards exposure. A national cross-sectional online survey was conducted. With the total population of Mauritians above the age of 20 years being 941,719, the calculated sample size was 400. A validated questionnaire was used to collect data among respondents from all 9 districts of the island of Mauritius, with representative district-wise samples. Data analysis was carried out using SPSS version 19.0. Considering the findings of the study, there were 408 respondents: Two-thirds of participants showed good knowledge of the harmful effects of SHS. Participants were aware of the link of SHS to respiratory diseases, nonetheless, they were not aware of its causes for non-respiratory diseases. One out of four participants (25.5%) were not aware that maternal passive smoking causes preterm delivery. More than one-third of the participants (37.3%) did not know that passive smoking causes sudden infant death syndrome. Inadequate levels of knowledge were also revealed by authors in other developing countries. We thus recommend bold sensitization campaigns about the serious threats of SHS. We highlight the pertinence of longitudinal cohort studies with assessment of SHS-related knowledge/behaviour before and after health education campaigns, in Mauritius and other developing countries.